The Evaluation of EU Cohesion Policy the Challenges for Poland in the Light of a New Budget - Drożyński, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
In order to remove regional economic disparities, the EU realizes a cohesion policy. The evaluation of the cohesion policy from the point of view of experiences of individual member states and the EU is not explicit. What is especially controversial here, are unsuccessful attempts to reach the main goal, which is social, economic and territorial cohesion. It does not mean the negation of outcomes of numerous researches which confirm a positive influence of the cohesion policy on the economic growth. The subject for a discussion is the right balance between the equality and effectiveness. The key issue is an answer to the question who and how to support. The question is whether the aid should be directed at areas which guarantee the highest added value? Should it be the priority to give equal opportunity to the poorest and to support them? At present the cohesion policy is trying to combine both those goals. However with the limited measures and rising social, economic and territorial disparities, those actions are ineffective. The main aim of the paper is an evaluation of the role of the EU cohesion policy in the stimulation of social-economic development, in particular in the light of a new EU budget.